2023
DOI: 10.15252/embj.2022111549
|View full text |Cite
|
Sign up to set email alerts
|

HERC3 promotes YAP/TAZ stability and tumorigenesis independently of its ubiquitin ligase activity

Abstract: YAP/TAZ transcriptional co-activators play pivotal roles in tumorigenesis. In the Hippo pathway, diverse signals activate the MST-LATS kinase cascade that leads to YAP/TAZ phosphorylation, and subsequent ubiquitination and proteasomal degradation by SCF b-TrCP . When the MST-LATS kinase cascade is inactive, unphosphorylated or dephosphorylated YAP/TAZ translocate into the nucleus to mediate TEAD-dependent gene transcription. Hippo signaling-independent YAP/TAZ activation in human malignancies has also been obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Therefore, UBE3C may be involved in efficiently transporting misfolded CFTR and ABCB1 to the proteasome for degradation, even without relying on its E3 ligase activity. This mechanism aligns with a model in which certain Ub ligases directly present the substrate protein to the 20S proteasome, facilitating their degradation and essentially acting as 'recruiters' [51][52][53].…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, UBE3C may be involved in efficiently transporting misfolded CFTR and ABCB1 to the proteasome for degradation, even without relying on its E3 ligase activity. This mechanism aligns with a model in which certain Ub ligases directly present the substrate protein to the 20S proteasome, facilitating their degradation and essentially acting as 'recruiters' [51][52][53].…”
Section: Discussionsupporting
confidence: 74%
“…7D). We further assessed the impact of GRK3 on TAZ, active-TAZ, YAP phosphorylation at Ser-381 (which recruits the SCFb-TrCP E3 ligase for ubiquitination dependent YAP degradation), and YAP phosphorylation at Ser-127 and TAZ at Ser-89 (which leads to their 14-3-3-dependent cytoplasmic sequestration) (27) . Western blot analysis demonstrated that GRK3 knockdown had no noticeable effect on these proteins and phosphorylation events (Fig.…”
Section: Trim58 Activates Grk3/hippo-yap Pathway Via Myh9mentioning
confidence: 99%
“…We found that CPNE3 modulates the YAP1 pathway without significantly affecting the expression of LATS1/2, an upstream regulator of YAP1, indicating that LATS kinase is not necessary for CPNE3 to regulate YAP1 [ 35 ]. Moreover, CPNE3 overexpression or deletion did not significantly change the expression of YAP1 mRNA, indicating that CPNE3 controls YAP1 function in GC cells by influencing post-transcriptional or protein degradation levels [ 36 , 37 ]. Here, we demonstrated that CPNE3 inhibits E3 ubiquitin ligase recruitment by competitively binding YAP1 to β-TRCP, prolonging the protein half-life of YAP1, and promoting YAP1 entry into the nucleus to activate the transcription of target genes downstream of the Hippo pathway, so forming a positive feedback loop [ 27 , 38 ].…”
Section: Discussionmentioning
confidence: 99%